DEVELOPING TRILINGUAL SMART BOOK MEDIA AS A LITERACY FACILITY FOR THIRD GRADE STUDENTS OF ELEMENTARY SCHOOL - Rita Umyati; Rina Yuliana; Odien Rosidin (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
his study aimed to develop trilingual smartbook media, to determine the feasibility of the trilingual smartbook, and to determine students' responses to trilingual smartbook. This research was conducted on 10 students at grade III of elementary school in a limited trial. This research utilized the Borg and Gall model which consisted of six stages, namely problem analysis, data collection, product design, design validation, design revision, and limited product trial. The instruments were a questionnaire sheet for product validation by expert lecturers and a questionnaire sheet for students' responses. Based on the analysis, the quality of the trilingual smartbook was categorized as very feasible with a percentage of 91% by two media experts, very feasible with a percentage of 92% by two material experts, and a feasible category with a percentage of 80% by two linguists. Moreover, the students' response to the trilingual smartbook was 96% with a very good category. Based on this, it can be said that the trilingual smartbook is appropriate to be used as a media of literacy facility for third grade elementary school students.